EQUIVALENT STIFFNESS RESEARCH OF THE ARC PERIODIC RAISED STRUCTURE PLATE - FENG Yan; DU GuoJun; MA YuJiao; GAO ChongYi (Jixie qiangdu)
According to the structure orthogonal anisotropic periodic raised structure plate,the equivalent stiffness of the arc periodic raised structure plate is investigated. Based on the classical theory of elastic thin plate and the homogeneous distribution characteristics of the plate,the analytic equation of the equivalent stiffness of the arc periodic raised structure plate is derived.The finite element method is used to simulate the numerical results of arc periodic raised structure plate with simply supported on Four Sides under the concentrated load. The rationality and accuracy of equivalent stiffness is verified. Then the natural frequency of the arc periodic raised structure plate under simply supported on four sides is calculated by using the analytic method. The calculation results are in agreement with the finite element simulation results,and the correctness of the analytical equation of the equivalent stiffness is verified again. The present new method can be used to calculate the equivalent stiffness of the periodic raised structure plate accurately. Moreover,the calculation is directly performed with the geometric parameters of the typical unit.This method is intuitive and concise,and improves the efficiency of solution. The results have important guiding significance for studying the static and dynamic characteristics of the periodic raised structure plate and engineering applications.